Chromatin proteomics reveals a dynamic histone code as novel druggable system essential to malaria parasite differentiation - Birkholtz, Lyn-Marie (University of Pretoria, 2022)
Thesis (PhD (Biochemistry))--University of Pretoria, 2021.